Effects of bamboo dietary fibre on meat semi-finished products - Rudyk, Viktor; Tyshchenko (Usatiuk), Olena; Usatyuk, Svitlana (My University, 2016)
The effects of bamboo fiber as a prospective fortificant of plant origin on the quality of meat semi-finished products were investigated.
Keywords: харчові волокна; волокна бамбука; функціональний інгредієнт; пищевые волокна; волокна бамбука; функциональный ингредиент; dietary fibre; bamboo fibre; functional ingredient; кафедра готельно-ресторанної справи; кафедра експертизи харчових продуктів